Manejo agronómico del cultivo de café (Coffe arábica L.) y su efecto en el rendimiento y calidad en su textura en el periodo 2018 – 2022. - Becilla Mora, Nayely Isabel (2023)
This document addressed the issue of agronomic management of coffee (Coffee arabica L.) and its effect on yield and quality in its texture in the period 2018 – 2022 This type of crop is produced in Ecuadorian territory. Because it presents anomalies that affect this type of crop, the main objective was to determine the importance of agronomic management in the cultivation of Arabica coffee for the yield and quality of its texture. A methodology with a qualitative approach and descriptive scope was proposed. In addition, for the preparation of this document, information was sought in updated texts, web pages, journals, scientific articles, virtual libraries and all valuable bibliographic material for the development of this research. The agronomic management has had deficiencies in Arabica coffee visualized by the changes analyzed since 2012 were high compared to later years but remain low until today. It was concluded that the agronomic management of the productive system such as phytosanitary processes, irrigation application, fertilization fractionation, sources and doses of fertilization, allow to demonstrate the parameters of quality and yield factor and it is recommended to be updated in science and technology.